Iodine excretion during stimulation with rhTSH in differentiated thyroid carcinoma - Löffler, M.; Weckesser, M.; Franzius, C.; Kies, P.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: Elevated iodine intake is a serious problem in the diagnostic and therapeutic application of 131iodine in patients with differentiated thyroid cancer. Therefore, iodine avoidance is necessary 3 months in advance. Additionally, endogenous stimulation requires withdrawal of thyroid hormone substitution for 4 weeks. Exogenous stimulation using recombinant human TSH (rhTSH) enables the continuous substitution of levothyroxine, which contains 65.4% of its molecular weight in iodine. Thus, a substantial source of iodine intake is maintained during exogenous stimulation. Although this amount of stable iodine is comparable to the iodine intake in regions of normal iodine supply, it may reduce the accumulation of radioiodine in thyroid carcinoma tissue. The aim of this study was to assess the iodine excretion depending on different ways of stimulation. Methods: Iodine excretion was measured in 146 patients in the long term follow up after differentiated thyroid carcinoma. Patients were separated into 2 groups, those on hormone withdrawal (G I) and rhTSH-stimulated patients on hormone substitution (G II). Results: Iodine excretion was significantly lower in hypothyroid patients (G I, median 50 μg/l, range: 25-600 μg/l) than in those under levothyroxine medication (G II, median 75 μg/l, 25-600 μg/l, p <0.027). TSH in G I (median 57.0 μU/ml, range: 14.4-183 μU/ml) was significantly lower (p <0.001) than in G II (117 μU/ml, 32.2-281 μU/ml). Conclusion: Iodine excretion was higher in patients under rhTSH-stimulation than after hormone withdrawal. This may indicate an increased iodine pool in rhTSH-stimulated patients (deiodination of levothyroxine), thus limiting the sensitivity of radioio-dine scanning to the level of endogenous stimulation despite significantly higher TSH levels during rhTSH-stimulation.
Keywords: Iodine excretion; rhTSH; differentiated thyroid carcinoma; thyroid hormone withdrawal; levothyroxine